Casa de piedra dam: effects of clear water on the river Colorado hydrography - Hector Walter Cazenave (Boletín Geográfico)
The construction of Casa de Piedra (Stone House) dam, in the final stretch of Colorado river high valley, radically modified down waters the hydrologic river course, especially regarding sediment transport, the majority of which settles in the lake. Consequently, waters the dam distributes, contain a remarkable erosive capacity, and accelerate down waters hydrographic processes, increasing river "meandering" and bringing about what is known as the ―clear waters phenomenon causing adverse effects on watering zones. With the purpose of checking the fact in a quantitative way, cartographies from a certain stretch were taken, being this stretch considered a witness one in periods around 25 years, assessing meanders appearance and disappearance, and comparing these quantities with the variation -in the same sense-, that took place since Casa de Piedra dam start up. The quantities were significant considering the relatively short time gone by. The fact was checked in a new aero - photographic flight, according to which, in a shorter lapse, meanders number increased again in the witness stretch.